Analysis of poor work postures during morning care operations of intensive care unit nurses: a field research - Junwei Lu; Jieli Li; Zhi Cheng; Honghong Wang; Su'e Yuan (BMC, 2024)
Abstract Background Poor working postures in morning care operations contribute significantly to work-related muscle fatigue and low back pain among ICU (Intensive Care Unit, ICU) nurses. However,there are few field studies on the relationship between Poor working postures and work-related muscle fatigue, low back pain among ICU nurses. Objective This study aims to assess the frequency and degree of posture hazards associated with poor working postures during morning care operations of ICU nurses. Methods Two ICUs in a Grade-A tertiary hospital in Hunan Province were randomly selected for the field study in May-June 2021 research. The image data of the participating nurses' morning care work postures were collected by observation method and image recording method, and the postural hazard level was assessed by the two-person interpretation method of the work posture analysis system. The mean and standard deviation, frequency and percentage were used for the basic statistical description, and the general linear model multivariate Hotelling's T 2 test was used to calculate the Hotelling's T 2 and F statistics to explore the pattern of change in the postural hazard score curves. Results A total of 45 nurses were observed during morning care operations, resulting in 47.8 h of video data and 34,428 effective static operation posture pictures. Among these pictures, 21,166 (61.5%) depicted poor working postures. Nurses spent up to 7 min and 30 s maintaining a challenging posture during oral care, with the highest postural hazard score (M = 2.2, SD = 0.3) observed during defecation care. Each patient requires a total of 25-30 min of oral care per day.The Hotelling's T 2 test indicated that the change curve of the postural hazard score in each step revealed the largest second-order F value, F = 52.931, P < 0.001. Discussion ICU nurses frequently adopt poor working postures during morning care operations. Further research should focus on optimizing safe working postures to prevent or minimise detrimental occupational hazards resulting from poor working postures.Research on occupational low back pain among ICU nurses can help them work more efficiently, and thereby improving their nursing level.